Signposts how to interpret the coincidences and symbols in your life - Linn, Denise (Rider, 1999)
The universe communicates to us through signs. Native peoples have always known how to interpret these powerful messages, but due to development of technology and increasing stress this skill has virtually been lost today. Learn how to reconnect with the magic of your inner self so that you too can interpret.